Chives—Allium schoenoprasum L. - James M. Stephens (EDIS)
This document provides an overview of chives (Allium schoenoprasum L.), highlighting their characteristics, uses, and cultivation methods. Chives are perennial plants with slender, tubular leaves and violet-colored flowers, native to northern Europe and parts of North America. They are valued for their delicate onion flavor, especially in salads, omelets, stews, and soups. The document details planting guidelines for Florida, recommending sets over seeds and advising on proper spacing and care. It also notes the practice of potting chives for indoor winter use in northern areas. Original publication date May 1994.